Carbon accumulation of Kandelia obovata (Sheue, Liu & Yong) plantation in the coastal area of Giao Thuy district, Nam Dinh province - Tuan, Mai Sy; Hong Hanh, Nguyen Thi (Academia Journal of Biology, 2012)
With a view to providing a scientific basis for evaluation of the role of mangrove plantation in reducing greenhouse gases - a foundation for the building and implementation of forest planting projects under Clean Development Mechanism (CDM) in Vietnam, a research has been undertaken on “Carbon accumulation of Kandelia obovata (Sheue, Liu & Yong) plantations of 1, 5, 6, 8 and 9 years old in Giao Lac commune, Giao Thuy district, Nam Dinh province. After a period of time of study, (from January 2005 to December 2007), we have figured out that Kandelia obovata plantation is able to accumulate a large amount of carbon, creating a carbon sink and contributing to decreasing CO2 in the atmosphere. The content of annually accumulated carbon of the plantation (corresponding to the content of CO2 credit) has increased with forest age. The accumulation is found the highest in 9 year old forest (27.138 ton/ha/year) equivalent to the amount of CO2 of 99.596 ton/ha/year (or 39.35%), 1.5 times as much as that of 8 year old plantation and 2.4 - 2.7 times as much as that of 6 and 5 year old plantations. The newly planted mangroves (1 year old) have also stored 2.207 tons of carbon/ha/year in trees and soil or 8.099 tons of CO2/ha/year (or 3.20%). The content of carbon accumulated in forest trees and soil is higher than the content of CO2 emitted; this is a scientific basis for the building and implementation of mangrove planting projects under CDM in coastal belts of Vietnam aimed at environmental protection, response to climate change, life improvement, hunger eradication and poverty alleviation for local people.